Big Data 29th British National Conference on Databases, BNCOD 2013, Oxford, UK, July 8-10, 2013. Proceedings - Gottlob, Georg; Grasso, Giovanni; Olteanu, Dan.; Schallhart, Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 29th British National Conference on Databases, BNCOD 2013, held in Oxford, UK, in July 2013. The 20 revised full papers, presented together with three keynote talks, two tutorials, and one panel session, were carefully reviewed and selected from 42 submissions. Special focus of the conference has been "Big Data" and so the papers cover a wide range of topics such as query and update processing; relational storage; benchmarking; XML query processing; big data; spatial data and indexing; data extraction and social networks.
Query and update processing -- Relational storage -- Benchmarking -- XML query processing -- Big data -- Spatial data and indexing -- Data extraction and social networks.
Keywords: Computer science; Software engineering; Data structures (Computer science).; Database management; Information storage and retrieval systems; Computer Science; Database Management; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Data Structures; Data Storage Representation; Software Engineering